Defect-free polymer multilayers prepared via chemoselective immobilization - Park, Mi-Kyoung (Langmuir : the ACS journal of surfaces and colloids, 2007)
In this paper, we investigated electrochemical properties of polymer multilayers on gold substrates using impedance spectroscopy. The multilayer was prepared by chemoselective ligation between aldehyde- and oxyamine-functionalized polymers via a layer-by-layer approach. The impedance spectra in a buffer solution in the absence of redox species revealed the formation of highly impermeable and defect-free films. The dielectric thickness of the polymer film, which is proportional to the reciprocal of capacitance, linearly increased as the number of deposition layer increased. The defect area of the polymer multilayer was obtained using the faradaic impedance with redox species. The surface coverage of eight polymer layers was determined to be 99.99%. Thus, the layer-by-layer deposition via chemoselective ligation offers a new way to prepare a highly insulating and defect-free polymer layer with finely tunable capacitance as a function of the number of deposition layers